Assessing the smartness of buildings. Issue 9 (6th July 2015) - Arditi, David; Mangano, Giulio; De Marco, Alberto
Abstract : Purpose: – This study aims at capturing the perspectives of construction professionals into a classified taxonomy of the various characteristics of smart buildings and at developing an index able to define their level of smartness. Design/methodology/approach: – A questionnaire survey has been administrated to construction professionals in the service of designers, constructors and owners. Results have been analyzed with the Kruskal–Wallis test and they have been used to develop a smartness index. Findings: – Designers and owners are more focused on the energy issue than constructors. The energy captures the attention of practitioners with less years of experience, confirming that the awareness of the energy topic is rather recent. Originality/value: – The main characteristics of smart buildings have been structured in domains and subdomains. Their importance has been rated by construction professional and a smartness index for smart building has been developed to provide with a convenient tool for evaluation and benchmarking.